The role of investment law in Indonesia's economic recovery efforts - Richart Sahatatua; Tri Setiady; I Ketut Astawa; Teuku Syahrul Ansari (Goodwood Publishing, 2024)
Purpose: This study examines the role of investment law in Indonesia's economic recovery efforts, particularly under Law No. 25 of 2007. Indonesia, as a developing country, emphasizes high economic growth as a measure of success in enhancing societal welfare. Investment, through capital investment, is crucial for increasing capital stock, production capacity, and economic growth, thereby creating jobs. Methodology: The study uses a normative legal research method with an analytical descriptive approach, analyzing regulations related to Law No. 25/2007, relevant literature, and data from the internet. Results: The findings indicate that legal certainty significantly influences investment decisions. A country with clear, fair, and well-enforced laws attracts more investors, which is essential for sustainable economic growth. Recent studies highlight the benefits and challenges of foreign direct investment (FDI) in Indonesia. Conclusion: Investment law strengthens legal certainty, boosts investor confidence, and supports Indonesia’s sustainable economic recovery through continuous reforms. Limitations: This study is limited to normative legal analysis with secondary data, excluding empirical evidence and international comparative perspectives. Contribution: Government efforts—regulatory reforms, legal enforcement, and infrastructure—foster a conducive investment climate. Continuous legal updates are essential to sustain investor confidence, ensure effectiveness, and support Indonesia’s economic growth.